2020
DOI: 10.4103/jcecho.jcecho_52_19
|View full text |Cite
|
Sign up to set email alerts
|

Anterior mitral leaflet perforation and infective endocarditis following transcatheter aortic valve replacement in a patient presenting with heart failure

Abstract: Transcatheter aortic valve replacement (TAVR) is an alternative treatment option for patients with severe aortic stenosis. Although rarely described, mitral valve perforation because of mechanical stimulation due to low deployment of the prosthesis and the association with infective endocarditis, are potentially life-threatening complications that physicians should be aware of because patients should not be suitable for further surgical or percutaneous management. Herein, we present a case of an 88-year-old ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Mitral valve perforation is a rare but well-known complication of TAVR, especially in cases of the low deployed valve. The mechanical abrasions from the contact of the prosthetic aortic valve with the anterior mitral leaflet can predispose the mitral valve to infective endocarditis and perforation [5]. It is still unclear in the literature whether endocarditis precedes mitral valve perforation or vice versa; nevertheless, Miura et al [6] described a case of anterior mitral leaflet perforation without infective endocarditis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mitral valve perforation is a rare but well-known complication of TAVR, especially in cases of the low deployed valve. The mechanical abrasions from the contact of the prosthetic aortic valve with the anterior mitral leaflet can predispose the mitral valve to infective endocarditis and perforation [5]. It is still unclear in the literature whether endocarditis precedes mitral valve perforation or vice versa; nevertheless, Miura et al [6] described a case of anterior mitral leaflet perforation without infective endocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of early and late infective endocarditis is almost equal among surgical aortic valve replacement and TAVR [5]. Based on the onset after the valve replacement, prosthetic valve endocarditis can be classified into early (within two months), intermediate (2 to 12 months), and late (>12 months) [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, our previous study found that in patients with pure native aortic valve regurgitation, 14 of 61 (23.0%) patients who received Venus-A prosthesis implantation had significant PAI following TAVR (18). To some extent, PAI should be considered a common complication (7,19,20), but it has rarely been described and is not covered by the VARC-3 criteria (16). In other words, the lack of consistent definitions and measurement standards in daily clinical practice has hindered the reporting of PAI.…”
Section: Discussionmentioning
confidence: 99%
“…Being in close contact at the level of the left fibrous trigone, the mitral valve may be exposed to significant changes in both geometry and structure due to mechanical alteration of the aortic root, changes that can potentially result in functional MR or exacerbate the impairment of a pathological mitral valve [20]. Although seldom described, anterior mitral leaflet perforation after TAVR is a well-known, potentially life-threatening complication after TAVR [21], also entailing the risk of subsequent infective endocarditis (IE) [22][23][24][25][26][27]. Considering the widespread use of TAVR, which in recent years has been established at a rapid pace as the standard of care for the management of patients with symptomatic severe aortic stenosis and high or prohibitive risk for standard surgical treatment, awareness should be raised regarding the vulnerability of the mitral apparatus, the mechanisms of its impairment, and the potential complications that may occur during TAVR procedures, in order to develop better strategies to avoid, recognize, and manage those complications [20,28].…”
Section: Introductionmentioning
confidence: 99%